Effect of yearly milk per cow on profitability of dairy herds - Edward P. Call; James R. Dunham (Kansas Agricultural Experiment Station Research Reports, 1993)
An analysis of Kansas Holstein herds in 1992 indicated that the yearly milk production per cow had a significant effect on returns to labor and management. The lowest quartile herds (13,445 lb per cow average) had a negative return to management. Herds averaging 20,614 lb per cow yielded 479 return to management. Records become increasingly important in managing the dairy operation, especially those that are readily analyzed and predict the degree of economic change when management is modified.; Dairy Day, 1993, Kansas State University, Manhattan, KS, 1993;
Keywords: Dairy Day; 1993; Kansas Agricultural Experiment Station contribution; no. 94-149-S; Report of progress (Kansas Agricultural Experiment Station); 694; Dairy; Milk production; Profit; Dairy cattle